2010
DOI: 10.1002/btpr.404
|View full text |Cite
|
Sign up to set email alerts
|

Inline ultrafiltration

Abstract: Inline ultrafiltration (UF) can significantly increase the recoverable mass of biopharmaceutical products when pool tank volumes are limiting. Using relatively small commercially available ultrafiltration cassettes, a proof-of-concept study demonstrates that inline UF can significantly increase recoverable mass in an antibody purification process. With ever-increasing cell culture titers pushing product masses to higher levels, inline UF offers a relatively easy-to-implement and less disruptive alternative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…One approach to intensify the AEX polishing step is to preconcentrate the feed. The use of a concentration step before chromatography has been described to reduce pool volumes and product load times for improved productivity and facility fit . In cases where conductivity reduction is required, concentration can help limit the volume expansion associated with dilution.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to intensify the AEX polishing step is to preconcentrate the feed. The use of a concentration step before chromatography has been described to reduce pool volumes and product load times for improved productivity and facility fit . In cases where conductivity reduction is required, concentration can help limit the volume expansion associated with dilution.…”
Section: Introductionmentioning
confidence: 99%
“…While the operation itself is simpler compared to TFF, the sieving behavior is more complicated. In case of completely retained proteins, SPTFF is already in place in industry to provide inline concentration of in‐process pools as reported in literature . One of the major limitations with SPTFF is the need to explore complicated staging arrangements or expand the membrane as higher concentrations are targeted, because the normalized feed flow rates are significantly lower (<10 L/h/m 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent analysis with a 5 g/L bioreactor titer indicated that buffer/product tank volumes would be the primary bottlenecks in the downstream process . A variety of solutions have been evaluated to address these bottlenecks: inline buffer dilution, in‐line product concentration, high‐capacity Protein A, and no‐salt hydrophobic interaction chromatography . These allow for incremental increases in the capacity of the existing purification trains; however, recent improvements in cell culture processes have allowed companies to achieve these higher titers with a shorter duration in the production bioreactor, forcing downstream development groups to explore ways to purify the product even more efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafiltration is utilized at the end of most purification processes to concentrate the product and exchange the product into the desired formulation buffer. It is most commonly operated in batch and fed‐batch mode with the product continuously recirculated; however, recent work has demonstrated that the same membranes can be operated in a single‐pass configuration by connecting multiple filters in series and continuously concentrating the product . We will explore the use of single‐pass tangential flow filtration (SPTFF) to concentrate harvested cell culture fluid (HCCF) and enable frozen storage for process decoupling between upstream and downstream processing.…”
Section: Introductionmentioning
confidence: 99%